Soft Ground Technology 2001
DOI: 10.1061/40552(301)14
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Assessment of Stabilized Soils

Abstract: The feasibility of using ultrasonic testing, in particular P-wave velocities, to evaluate stabilized soils was investigated. A high-plasticity clay soil that was stabilized with lime, cement, and lime -fly ash mixtures was used in the study. The testing program consisted of determination of P-wave velocities and compression characteristics of the stabilized soils immediately after compaction and subsequent to 7 days and 28 days of curing. Variation of velocity with stabilizing agent, curing time, and also with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Importantly, the UPV values were lower than that observed in experiments using additives other than fly ash and lime [74]. This reveals the uniquely low performance of WMP, attributed to its fine particle size and chemical reactivity.…”
Section: Upv Impactsmentioning
confidence: 69%
See 1 more Smart Citation
“…Importantly, the UPV values were lower than that observed in experiments using additives other than fly ash and lime [74]. This reveals the uniquely low performance of WMP, attributed to its fine particle size and chemical reactivity.…”
Section: Upv Impactsmentioning
confidence: 69%
“…The UPV enhancement directly correlates with the measured gains in density and strength, validating UPV testing to characterize soil stabilization effectiveness. Importantly, the UPV values were lower than that observed in experiments using additives other than fly ash and lime [74]. This reveals the uniquely low performance of WMP, attributed to its fine particle size and chemical reactivity.…”
Section: Upv Impactsmentioning
confidence: 69%
“…Mandal et al (2016) documented similar test results. Besides, Yesiller et al (2000) reported that the wave velocity of cement-treated soil specimens was higher than the wave velocity of the natural specimens.…”
Section: Wave Velocity Resultsmentioning
confidence: 99%
“…Indirectly, the speed of the waves will be affected by the water content of the material [45]. That is why higher wave propagation velocities can be observed in stabilized soils [42,46,47]. Wave velocities are often correlated with unconfined compressive strength [48,49].…”
Section: Introductionmentioning
confidence: 99%